2016
DOI: 10.1016/j.jped.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Fat mass index performs best in monitoring management of obesity in prepubertal children

Abstract: FMI achieved the best combination of ability and swiftness to identify reduction of adiposity during monitoring of weight management in prepubertal obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
2
7
0
1
Order By: Relevance
“…Using the FMI Class-II definition, the prevalence of fat in both genders (boys: 19.7%; girls: 13.1%) was much higher than that defined by the BMI (boys: 13.2%; girls: 7.1%). This result corresponds with a previous study showing that FMI better discriminates adiposity than BMI [ 11 ]. We used Korean reference values due to a lack of available FMI data among Taiwanese children and adolescents, but the FMI of both girls and boys in our study was much lower than those of the Korean subjects in each subgroup classified by age.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using the FMI Class-II definition, the prevalence of fat in both genders (boys: 19.7%; girls: 13.1%) was much higher than that defined by the BMI (boys: 13.2%; girls: 7.1%). This result corresponds with a previous study showing that FMI better discriminates adiposity than BMI [ 11 ]. We used Korean reference values due to a lack of available FMI data among Taiwanese children and adolescents, but the FMI of both girls and boys in our study was much lower than those of the Korean subjects in each subgroup classified by age.…”
Section: Discussionsupporting
confidence: 92%
“…Since BMI reflects both the fat mass (FM) and the fat-free mass (FFM) in the body, it might be poorly correlated with %FM in children and adolescents [ 10 ]. Studies have also shown that FM index (FMI), defined as FM (kg) divided by height squared (m 2 ), better discriminates adiposity compared to BMI [ 11 ] and %FM [ 12 ]. Studies are showing now that a higher FMI, like a higher BMI and increased %FM, is associated with CV diseases [ 13 ] and metabolic syndrome [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another limitation of this study was not adjusting fat mass to an unrelated measure of body fat such as height that could improve interpretation when assessing adiposity [42]. In children, the fat mass index was demonstrated to better discriminate adiposity than the BFP [43,44]. Another limitation of the study was the fact that the accuracy of muscle mass (%) measurement by the device used in this study was unknown, and the socioeconomic status of the parents of the preschoolers was not included in the analyzes.…”
Section: Discussionmentioning
confidence: 98%
“…The use of FMI (when compared to FM% alone) has been proposed as a more accurate indicator of adiposity and more sensitive to changes in body fat stores [35, 47], even in infants [48], due to the consideration and normalization to height/length [27, 49]. Infants at potential risk (but with “normal” BMI) could be detected using FMI [48] because it better identifies excess adiposity than FM%, which underestimates it [35].…”
Section: Discussionmentioning
confidence: 99%